2015
DOI: 10.1111/gtc.12222
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeranyltransferase Cwg2‐Rho4/Rho5 module is implicated in the Pmk1 MAP kinase‐mediated cell wall integrity pathway in fission yeast

Abstract: Pmk1, a fission yeast homologue of mammalian ERK MAPK, regulates cell wall integrity, cytokinesis, RNA granule formation and ion homeostasis. Our screen for vic (viable in the presence of immunosuppressant and chloride ion) mutants identified regulators of the Pmk1 MAPK signaling, including Cpp1 and Rho2, based on the genetic interaction between calcineurin and Pmk1 MAPK. Here, we identified the vic2-1 mutants carrying a mis-sense mutation in the cwg2 + gene encoding a beta subunit of geranylgeranyltransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…We then examined the combined effect of FK506 and MgCl 2 on Δskb5 and Δpmp1 cells. Our previous findings established that the vic phenotype (for 'viable in the presence of chloride ion') is a strong indicator of MAPK signaling inhibition (Ma et al, 2006a,b;Doi et al, 2015). The results showed that Δskb5 and Δpmp1 cells failed to grow in medium containing 0.06 M MgCl 2 and FK506, whereas the WT cells grew in this medium, indicating that Skb5 deletion induced a vic-negative phenotype (Fig.…”
Section: Skb5 Overproduction Negatively Regulates Pck2-pmk1 Mapk Signmentioning
confidence: 62%
See 1 more Smart Citation
“…We then examined the combined effect of FK506 and MgCl 2 on Δskb5 and Δpmp1 cells. Our previous findings established that the vic phenotype (for 'viable in the presence of chloride ion') is a strong indicator of MAPK signaling inhibition (Ma et al, 2006a,b;Doi et al, 2015). The results showed that Δskb5 and Δpmp1 cells failed to grow in medium containing 0.06 M MgCl 2 and FK506, whereas the WT cells grew in this medium, indicating that Skb5 deletion induced a vic-negative phenotype (Fig.…”
Section: Skb5 Overproduction Negatively Regulates Pck2-pmk1 Mapk Signmentioning
confidence: 62%
“…Our previous genetic screen for negative regulators of Pmk1 MAPK signaling identified phosphatases (Sugiura et al, 1998) that inactivate MAPK signaling, including the Pmp1 dual-specificity phosphatase and the PP2C serine/threonine protein phosphatase (Takada et al, 2007) in addition to the Rnc1 RNA-binding protein (Sugiura et al, 2003) and the cell surface protein Ecm33 (Takada et al, 2010). Our genetic screen also identified components and activating regulators of Pmk1 MAPK, including the small GTPases Rho1, Rho2, Rho4 and Rho5, and the protein kinase C (PKC) protein Pck2, by isolating mutants of the farnesyl transferase Cpp1 and geranylgeranyl transferase Cwg2 (Ma et al, 2006a,b;Doi et al, 2015). Here, we have established a novel genetic screen for negative regulators of Pck2-mediated MAPK signaling activation by utilizing the cell growth defect induced by Pck2 overproduction and its recovery upon Pmk1 signaling inhibition (Takada et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Rho5 acts as a functional homologue of rho1, sharing the role of regulating cell wall homeostasis 46. More recently, rho5 has also been shown to be an upstream regulator of the CWI 47. The regulation of this pathway is complex as Rho1 both positively 45 and negatively 48 regulates the downstream MAP kinase cascade.…”
Section: Discussionmentioning
confidence: 99%
“…These include upstream activating regulators of MAPK signaling such as geranylgeranyl transferase (Doi et al . ), farnesyl transferase (Ma et al . ), negative regulators of MAPK signaling such as MAPK phosphatases (Sugiura et al .…”
Section: Introductionmentioning
confidence: 99%
“…This screen has successfully identified several components and regulators of the Rho/ PKC/MAPK signaling pathway. These include upstream activating regulators of MAPK signaling such as geranylgeranyl transferase (Doi et al 2015), farnesyl transferase (Ma et al 2006), negative regulators of MAPK signaling such as MAPK phosphatases (Sugiura et al 1998) and an SH3-domain adaptor protein (Kanda et al 2016), and MAPK substrates including RNA-binding proteins (Sugiura et al 2003;Satoh et al 2009Satoh et al , 2017 and transcription factors (Takada et al 2007). These results prompted us to develop a novel cell-based yeast phenotypic screen for identifying compounds that target MAPK signaling and have the potential for regulating MAPKrelated processes in higher organisms through monitoring of the suppression of the Cl À -sensitive growth defect of CN KO cells (Sugiura et al 2012).…”
Section: Introductionmentioning
confidence: 99%